2010
DOI: 10.1080/01446193.2010.480976
|View full text |Cite
|
Sign up to set email alerts
|

A definition and valuation of the UK offsite construction sector

Abstract: The offsite construction sector is now established as a significant contributor to the delivery of UK construction industry output. The exact value of this contribution is questionable and has been subject to substantial debate in recent literature. Existing offsite construction sector valuation methodologies have been based upon market research questionnaires and estimates of turnover and manufacturing output. Considerable attention has been given to the definition of the terms used to describe the various co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 10 publications
0
57
0
2
Order By: Relevance
“…The industrialisation of housing production have learned from other manufacturing processes and have gained benefits by managing the entire production system from supply-chain management to factory production to sales and on-site activities with adequate balance of standardisation and flexibility (Gann 1996). In fact, the off-site construction is seen to have paramount significance for the efficiency (Taylor 2010). 336 management · volume 13 Nevertheless, product configurability has been considered in the construction context with product family type decomposition that is opened to system and subsystem levels, and modules and components (Jensen, Lidelöw, and Olofsson 2015). Configurability of construction service products has not been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The industrialisation of housing production have learned from other manufacturing processes and have gained benefits by managing the entire production system from supply-chain management to factory production to sales and on-site activities with adequate balance of standardisation and flexibility (Gann 1996). In fact, the off-site construction is seen to have paramount significance for the efficiency (Taylor 2010). 336 management · volume 13 Nevertheless, product configurability has been considered in the construction context with product family type decomposition that is opened to system and subsystem levels, and modules and components (Jensen, Lidelöw, and Olofsson 2015). Configurability of construction service products has not been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The market value of offsite in UK construction is hard to determine, but has been estimated up to £6bn (see Taylor 2010), equivalent to a less than 6% share in UK construction with an annual output worth over £100bn (BERR 2008). A recent survey of leading UK housebuilders by Pan et al (2008) confirmed that the level of overall application of offsite in housebuilding was also low.…”
Section: Offsite Production In Housebuildingmentioning
confidence: 99%
“…Introduction Much excitement surrounds off-site construction, as the introduction of techniques such as prefabrication and modularisation, over time, begin to resolve the productivity limitations of traditional on-site construction (Alazzaz and Whyte, 2012). The off-site construction industry is burgeoning; in the UK, for example the total gross output of the off-site construction sector rose from £2.3 billion in 1998 to £5.8 billion in 2008, albeit for only 2.1 per cent of the total value of construction activities (Taylor, 2010). A main reason for industry's endorsement of off-site production methods appears to be a perceived improvement in productivity (Bernstein et al, 2011).…”
mentioning
confidence: 99%